Strategi Penanganan Penyandang Masalah Kesejahteraan Sosial (PMKS) di Kabupaten Rokan Hilir (Studi Kasus Orang Dengan Gangguan Jiwa) - Dini Safitriani; Abdul Sadad (Journal of Research and Development on Public Policy, 2023)
A person with Social Welfare Problems (PMKS) is a family or community group who due to an obstacle, difficulty or disorder, is unable to carry out their social functions, so that they cannot meet their life needs (physical, spiritual, and social) adequately and reasonably, these obstacles, difficulties and disorders can be in the form of poverty, displacedness, disability, social decency, backwardness, alienation and environmental changes (suddenly) that are lacking supportive, such as the occurrence of disasters. Therefore, the Social Service as an element that organizes local government affairs with the authority of decentralization and deconcentration in the fields of protection, social security, services, social rehabilitation, social empowerment of the poor provides direct services to protect, redability and empower as well as meet the basic needs of PMKS. The purpose of this study is to find out how the strategy of handling people with mental disorders in Rokan Hilir and to find out the inhibiting factors in handling people with mental disorders in Rokan Hilir Regency. This research uses descriptive qualitative methods, and data collection techniques, namely interviews and documentation. The Strategy for Caring for Persons with Social Welfare Problems (PMKS) case study of People with Mental Disorders (ODGJ) in Rokan Hilir Regency, it can be concluded that the Stretegi currently carried out by the Social Service Office is already running, the focus of the strategy carried out is still on mental rehabilitation and although the program is running well, there are obstacles faced, namely the lack of funds and lack of community participation. This is explained in the indicators of the Mintzberg, Lampel, Quinn, Ghospal theory indicators, namely Objectives, Policies, Programs. But there are still inhibiting factors, namely the lack of budget for handling people with mental disorders (ODGJ) in Rokan Hilir Regency, lack of public understanding of the ODGJ Treatment Program. It is hoped that in the future the need to increase welfare and support for ODGJ aims to provide a focus in preventive efforts to prevent mental health problems, the allocation of funds from the Regional Government of Rokan Hilir Regency, especially for handling ODGJ, is expected to be more optimal and the Social Service is expected to be able to carry out outreach programs for ODGJ more evenly.